Order effects in transitive inference: does the presentation order of social information affect transitive inference in social animals? - Hotta, Takashi; Jordan, Lyndon A.; Takeyama, Tomohiro; Kohda, Masanori (Frontiers in Ecology and Evolution, 2015)
Transitive inference (TI) is the ability to infer social relationships between individuals (e.g. if A<B & B<C, then A<C), and has been documented in a variety of vertebrates. Many studies of TI use the task of inferring social dominance, where a subject animal A first interacts with B (e.g. A subordinate to B: A<B), and then observes the interaction of B and an unknown C (B<C), thereby inferring its own relationship with C (A<C). However, order effects are known to influence learning, especially in complex scenarios, and we do not know whether transitive inference depends on presentation order of social experiences, for any animal. Here we show that the cichlid Julidochromis transcriptus can correctly perform TI when social information is presented in the order opposite to that established in the literature. We find that focal individuals (A) can transitively infer their relationships with an unknown individual (C) when initially given indirect experience (i.e. eavesdropping that B<C) and then given direct experience (A<B). We conclude that J. transcriptus can infer social relationships independent of social information presentation order. We suggest that in this and many other species, transitive inference may occur in either presentation order, and future studies of TI should account for order effects of social information.